The Concept And Development Of Literary Image (Obraz) Theory - Achilova Gulhayo Ismoilovna (Academia One, 2025)
This article examines the concept and evolution of the literary image (obraz) in world literary theory and aesthetics. Beginning with its etymological roots, the study explores the interpretations of “image” in classical philosophy, including Aristotle’s notion of mimesis, Hegel’s view of art as “thinking through images,” and Kant’s epistemological approach. The paper further analyzes Sigmund Freud’s psychoanalytic perspective, emphasizing the role of unconscious processes in image formation. The contributions of Russian literary critics such as Belinsky, Bakhtin, and Shklovsky are discussed, along with Roland Barthes’ poststructuralist approach, which challenges the author’s authority in interpretation. Finally, the article addresses the integration of the term obraz into Uzbek literary studies, replacing earlier concepts such as “timsоl, tasvir, and nusxa”. The study concludes that the image, as a central category in literary theory, serves as a bridge between reality and imagination, uniting aesthetic, social, psychological, and cultural functions
Keywords: Obraz”literary image; mimesis; catharsis; aesthetic theory